Complete Blood Count Parameters and Hemogram-Derived Inflammatory Indices in Adolescent Pregnancy: A Retrospective Comparative Cohort Study with Exploratory Machine-Learning Analyses - Meryem Bekmezci; Ramazan Bülbül; Şerife Özlem Genç; Hüseyin Erdal (Journal of Clinical Medicine, 2026)
Background/Objectives: Adolescent pregnancy is associated with an increased risk of adverse perinatal outcomes; however, its hematological characteristics remain incompletely understood. The aim of this study was to compare antepartum and postpartum complete blood count (CBC) parameters together with hemogram-derived inflammatory indices in adolescent and adult pregnancies and to investigate their associations with maternal and neonatal outcomes. Methods: This retrospective comparative cohort study included 428 singleton pregnancies comprising 205 adolescent (14–17 years) and 223 adults (18–42 years). Antepartum blood samples were obtained at admission for delivery, whereas postpartum samples were collected approximately six hours after delivery according to the institutional practice. CBC parameters (including neutrophil, lymphocyte, monocyte, and platelet counts) were recorded, and hemogram-derived inflammatory indices, including neutrophil-to-lymphocyte ratio (NLR), Platelet-to-lymphocyte ratio (PLR), systemic immune-inflammation index (SII), systemic inflammation response index (SIRI), aggregate index of systemic inflammation (AISI), and systemic inflammation-monocyte index (SIMI), were subsequently calculated. Comparisons were adjusted for gestational age at sampling and parity using a prespecified non-redundant marker set, and multiple testing was controlled using the Benjamini-Hochberg false discovery rate procedure. Multivariable logistic regression and machine-learning analyses were performed to evaluate associations with adverse maternal and neonatal outcomes. Results: Adolescent pregnancies demonstrated significantly higher antepartum neutrophil and monocyte counts than adult pregnancies (q < 0.05), and these differences remained significant after adjustment for gestational age at sampling and parity (both q < 0.01), whereas differences in hemoglobin and platelet counts were no longer significant (both q = 0.138). Low birth weight (10.2% vs. 4.5%), neonatal intensive care unit admission (15.1% vs. 8.5%), composite adverse outcome (22.9% vs. 15.2%), and birth weight below the 10th percentile (14.7% vs. 8.0%) were numerically more frequent among adolescents but were not statistically significant after false discovery rate correction (all q > 0.05). Across 30 prespecified marker–outcome associations, none remained significant after false discovery rate correction. Antepartum neutrophil count was not independently associated with low birth weight after multivariable adjustment (OR 1.233, 95% CI 0.858–1.737; p = 0.248, q = 0.413). Exploratory machine-learning models demonstrated only modest discrimination, with the highest cross-validated AUC of approximately 0.60, and did not outperform conventional regression models. Conclusions: Adolescent pregnancy was associated with higher neutrophil and monocyte counts during both the antepartum and postpartum periods, reflecting modest differences in hematological profile rather than an independently predictive inflammatory profile. These hematological differences were not independently associated with adverse maternal or neonatal outcomes after adjustment for confounding factors and correction for multiple testing. Hemogram-derived inflammatory indices should therefore be interpreted as mathematical transformations of routine CBC parameters rather than biologically independent biomarkers. Because blood samples were obtained at admission for delivery, these findings characterize the peripartum inflammatory profile and should not be interpreted as evidence of early pregnancy risk prediction.